Pelatihan Pembuatan Pupuk Organik Cair Dari Limbah Cair Kulit Buah Kopi Sebagai Pendukung Pertumbuhan Tanaman - Putri Ariyani, Tasya Vyra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Coffee is one of the most popular plantation products. Indonesia is the fourth largest country as the largest coffee producer in the world. One of the coffee producing areas in Indonesia is Kalipucang Village, which is located on the slopes of Mount Bromo in East Java. The coffee bean processing process generally produces several by-products. Coffee skin is one of the by-products of the coffee processing process to become coffee beans that are ready for consumption. Generally, coffee skins are not used because they do not have a selling value like coffee beans. To increase the selling value of the by- product in the form of coffee skin, the coffee skin is used as an organic fertilizer. The main method used in making this organic fertilizer is fermentation at room temperature and anaerobes condition. This organic fertilizer product can be used for various plant.